Brønsted acid-promoted hydroamination of unsaturated hydrazones: access to biologically important 5-arylpyrazolines. Issue 28 (11th May 2021) - He, Han; Xu, Ning; Zhang, Honglin; Chen, Bin; Hu, Zhengnan; Guo, Kang; Chun, Jianlin; Cao, Shujun; Zhu, Yingguang
Abstract : An efficient, chemo- and regioselective Brønsted acid-promoted hydroamination reaction of hydrazone-tethered olefins towards 5-arylpyrazolines was developed. Abstract : A novel and efficient Brønsted acid-promoted hydroamination of hydrazone-tethered olefins has been developed. A variety of pyrazolines have been easily obtained in good to excellent yields with high chemo- and regioselectivity under simple and mild conditions. This method represents a straightforward, facile, and practical approach toward biologically important 5-arylpyrazolines, which are difficult to access by previously reported radical hydroamination of β, γ-unsaturated hydrazones.